2022
DOI: 10.1115/1.4055642
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Turbine Operating Conditions on Combustor–Turbine Interaction—Part I: Change in Expansion Ratio

Abstract: Aeroengine lean-burn combustors release vorticity and temperature perturbations that, interacting with the first turbine stage, impact the stage aerodynamics, blade cooling and noise production. The first of these issues is addressed in this paper that is part 1 of a two-fold contribution. A detailed experimental analysis is carried out to study the impact on the combustor-turbine interaction of the off-design conditions experienced by aero-engines in their duty. Engine-representative disturbances are generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…However, entropy noise is not strictly associated with the aerodynamic and heat transfer problems discussed in the present paper and is not going to be detailed here. For those who are interested in studying this challenging topic, the works by Gaetani and Persico [58], Gaetani et al [59], Pinelli et al [60], Notaristefano and Gaetani [61,62,63], and Pinelli et al [64] are suggested.…”
Section: Hot Spot Migration In the High-pressure Turbine Stagementioning
confidence: 99%
“…However, entropy noise is not strictly associated with the aerodynamic and heat transfer problems discussed in the present paper and is not going to be detailed here. For those who are interested in studying this challenging topic, the works by Gaetani and Persico [58], Gaetani et al [59], Pinelli et al [60], Notaristefano and Gaetani [61,62,63], and Pinelli et al [64] are suggested.…”
Section: Hot Spot Migration In the High-pressure Turbine Stagementioning
confidence: 99%
“…At the outlet of the injector, a swirl generator is placed that acts on both the mainstream air and the steady/unsteady generated disturbances. Further details of the combustor simulator are described in Notaristefano and Gaetani (2020).…”
Section: Generated Combustor Disturbancesmentioning
confidence: 99%
“…In this context, many combustor simulators (used by Andreini et al (2016), Werschnik et al (2017), Notaristefano and Gaetani (2020) and Adams et al (2021)) were conceived to mimic, by nonreactive devices, the combustor released flow and to allow the experimental testing and numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations